Improving Knowledge Sharing in Organizations - Tini Mogea (Universitas Maritim AMNI Semarang, 2023)
Knowledge sharing is a very important part of knowledge management. This article is a literature study on the factors that influence knowledge sharing in organizations. Based on a literature study conducted on the results of research on the factors that influence knowledge sharing in organizations, several factors that influence knowledge sharing are found. These factors are then analyzed and categorized based on aspects of organizational control. Factors that are within the control of the organization amounted to 13 factors. Then this article discusses more about the factors that are within the control of the organization and steps that can be taken by the organization to increase knowledge sharing.